A Theory of the Syndicate: Form Follows Function - Pichler, Pegaret; Wilhelm, William (Journal of Finance, 2001)
ABSTRACT We relate the organizational form of investment banking syndicates to moral hazard in team production. Although syndicates are dissolved upon deal completion, membership stability across deals represents a barrier to entry that enables the capture of quasirents. This improves incentives for individual bankers to cultivate investor relationships that translate into greater expected proceeds. Reputational concerns of lead bankers amplify the effect. We derive conditions under which restricted entry and designation of a lead banker strictly Pareto dominate, in which case it is also strictly Pareto dominant for the syndicate's fee to be greater than members' cost of participation.